Shaping Learning Through Narratives: Pre-service Teachers’ Experiencesin Simulated Curriculum Design and Material Development - Anne Lou M. Hendriks (LPPM Universitas Advent Indonesia, 2026)
This qualitative study investigates pre-service teachers’ experiences with simulated curriculum design and material development, focusing on how these activities contribute to their professional growth, problem-solving skills, creativity, and reflective practice. Five pre-service teachers who completed a Curriculum Design and Material Development course participated through written narrative responses. Data were analyzed using thematic narrative analysis to identify patterns and overarching themes, which revealed four key areas: developing professional identity through simulation, navigating challenges and problem-solving, creative and strategic curriculum and material design, and reflective learning and meaning-making. The findings suggest that simulation-based, practice-oriented experiences offer a safe environment for experimentation, foster critical reflection, and enhance pre-service teachers’ readiness to design effective curricula and instructional materials. Bottom of FormThese findings highlight the importance of integrating experiential and narrative approaches in teacher education to enhance professional development and pedagogical competence.